2009
DOI: 10.1088/1674-1137/33/6/001
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of self-affine multiplicity fluctuation of target residues in 84 Kr-AgBr interactions at 1.7 AGeV

Abstract: Self-affine multiplicity scaling is investigated in the framework of a two-dimensional factorial moment methodology using the concept of the Hurst exponent (H). Analyzing the experimental data of target evaporated fragments emitted in 84Kr-AgBr interactions at 1.7 AGeV revealed that the best power law behavior is exhibited for H = 0.3 indicating a self-affine multiplicity fluctuation pattern. A signal of multifractality is also observed from knowledge of the anomalous fractal dimension dq extracted from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…From the plot it is seen that d q is linearly dependent on order q, which suggests the presence of multifractality of emission of medium-energy knocked-out protons in 84 Kr-AgBr interactions. It is the same as our previous result on target residue production in 84 Kr-AgBr interactions at the same energy [27] . It has been suggested that self-similar cascade can occur in different phases [28] , namely the normal phase populated by many relatively small fluctuations and the spin glass phase consisting of few very large fluctuations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…From the plot it is seen that d q is linearly dependent on order q, which suggests the presence of multifractality of emission of medium-energy knocked-out protons in 84 Kr-AgBr interactions. It is the same as our previous result on target residue production in 84 Kr-AgBr interactions at the same energy [27] . It has been suggested that self-similar cascade can occur in different phases [28] , namely the normal phase populated by many relatively small fluctuations and the spin glass phase consisting of few very large fluctuations.…”
Section: Resultssupporting
confidence: 89%
“…84 Kr-AgBr interactions at 1.7 AGeV [27] . Target recoil protons (gray particles) and target residues (black particles) originate from the target, but with different energies and production mechanisms.…”
Section: Resultsmentioning
confidence: 96%